KOMUNIKASI SENI MADIHIN SEBAGAI KESENIAN MASYARAKAT SUKU BANJAR DI TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Dewi Afrilina; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Madihin is a art Kalimantan Selatan poetry or bounce accompained music with blow music rebana called tarbang. Madihin art in Tembilahan already available before Indonesia Independence. This art developing in Tembilahan city because happened big immigration Kalimantan Selatan Banjar society to Tembilahan last era 19 ago in 1999. The purpose of this study was to determine the communication process Madihin, speech act art communication madihin, and message meaning art communication madihin.This research uses qualitative method using with purposive methods by iterviewing 10 informant. The theory used is the theory of symbolic interaction with an ethnographic approach to communication. Data collection techniques with interviews, observation, and documentation. Data analysis techniques use the Miles and Hubermen models. To achieve data validity, reseaarches used extended participation and tringulation.The results of the study show that the process of communication of madihin art in Tembilahan, Indragiri Hilir Regency consists of preparation and implementation. At the preparation stage that must be prepared is mental, clothing and musical instruments. At the implementation stage consists of four, namely opening, respect, content and closing The communication speech act contained in the madihin poem is the act of locution to inform something, the act of illocution to convey something that has a purpose and purpose in it, the act of perlokusi is the effect arising from poetry. The meaning of the message in madihin consists of two, namely as advice and humor. Advice in madihin consists of marriage, education and religious advice. Humor contained in madihin serves as entertainment and as learning.